Caracterização geofísica e geológica das formações ferríferas do Grupo Macaúbas - MG - Mario, André Felipe Gonçalves de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The iron ore prospects of Macaúbas Basin were studied in this research aimed to define their rock types, classification, depositional environment, genesis, occurrence area and their respective potential exploration. These occurrences were classified as belonging to three distinct geological formations, being able to highlight the occurrences of ferriferous metadiamictites on Riacho Poções Member (Nova Aurora Formation), which have been described, detailed and divided into two types, called metadiamictites hematitic and ferruginous, being this mineralization related to the glacial deposits classified as type Rapitan. Other occurrences of iron formations have been identified in the south of the Nova Aurora Formation, being the first related to a phyllite sequence from graphitic to ferruginous with sulfide levels (pyrite and chalcopyrite), characterized in this study as a new unit, called Catutiba Formation. In the southern portion of the basin, was described a sequence of banded iron formations, the siliciclastic type, in the midst a unit of ferruginous quartzites belonging to the Superior Member of the Capelinha Formation, which is the last manifestation of iron deposition in the basin that was classified as a siliciclastic sequence. The mineralization is regionally controlled by foliation S1, with approximate direction N30E direction to dip to SE, being defined three phases of mineralization to these events. The first one related to iron deposition in the basin, the second one related to the tectonic-metamorphic concentration during the phase of deformation that generated the S1 foliation, folds, faults and shear zones controlling the mineralization that will suffer later in a third phase, the action of supergene concentration processes in the plateau regions. Has been estimated that these iron ore occurrences have an exploration potential of around 55 billion cubic meters with an average grade of 20% to 25% iron, reaching levels of ...

Os prospectos de minério de ferro da Bacia Macaúbas foram estudados nessa pesquisa que objetivou definir os seus litotipos, classificação, ambiente de deposição, gênese, área de ocorrência e seus respectivos potenciais de exploração. Essas ocorrências foram classificadas como pertencentes a três formações geológicas distintas, podendo-se dar destaque ao metadiamictito ferrífero do Membro Riacho Poções (Formação Nova Aurora), que foram detalhados e divididos em dois tipos, denominados de metadiamictito hematítico e ferruginoso, estando essa mineralização relacionada a depósitos glaciais, classificados como tipo Rapitan. Outras ocorrências de formações ferríferas foram identificadas ao sul da Formação Nova Aurora, estando a primeira relacionada a uma sequência de filito, de grafitoso a ferruginoso com níveis sulfetados (pirita e calcopirita), caracterizados pelo autor neste estudo como uma nova unidade, chamada Formação Catutiba. Na porção sul da bacia, descreveu-se uma sequência de formações ferríferas bandadas, do tipo siliciclástica, em meio a uma unidade de quartzito ferruginoso, pertencente ao Membro Superior da Formação Capelinha, sendo esta a última manifestação de deposição de ferro na bacia que foi classificada como sendo uma sequência siliciclástica do tipo acamadada. As mineralizações estão controladas regionalmente pela foliação S1, de direção aproximada N30E com mergulho para SE, sendo definidas três fases de mineralização para essas ocorrências, a primeira relacionada à deposição do ferro na bacia, a segunda relacionada à concentração tectono-metamórfica durante a fase de deformação que gerou a foliação principal que controla a mineralização, dobras, falhas e zonas de cisalhamento que controlam a mineralização que sofrerão posteriormente, em uma terceira fase, a ação de processos de concentração supergênica nas regiões de platô. Estimou-se que estas..
Keywords: Geology, Structural; Geologia estrutural; Minerios de ferro; Formações (Geologia); Minas Gerais